Preliminary study on the utilization of cabbage waste as a raw material for activated carbon in supercapacitor applications - Syahputri, Intan; Awitdrus, Awitdrus (Indonesian Physics Communication, 2025)
This study aims to utilize cabbage waste as an active carbon material for supercapacitor electrodes through an environmentally friendly approach without chemical activation. The fabrication process includes pre-carbonization at 200°C for 1 hour, carbonization at 600°C, and physical activation at 850°C. The resulting carbon material exhibits a porous structure essential for ion storage, despite the absence of chemical activation. Electrochemical testing using the galvanostatic charge-discharge method with Na2SO4 electrolyte concentrations of 0.5 M, 1 M, and 1.5 M demonstrated a highest specific capacitance of 155.87 F/g at 1.5 M concentration. The increase in electrolyte concentration enhances ion mobility and charge storage capacity. This research indicates that cabbage waste can serve as an effective active carbon source for supercapacitors, with further performance improvements expected through chemical activation in future studies.